Atom/molecule transportation using a dark soliton pulse - Vongchumyen, C.; Authasing, S.; Mitatha, S.; Ali, J.; Yupapin, P. P. (My University, 2010)
A dark soliton pulse beam that has potential applications in the probing and transport of atoms or molecules as an optical tweezers is demonstrated. The trap pulse beam is formed in the gap between a BP signal at 1500.00 nm and Stokes signal at 1500.09 nm, which have peak powers of -12 dBm. The generated beam is seen to be stable with no fluctuations over a test period of 10 minutes, which is important to ensure that the transported atom / molecule is not lost in the link media. ©2010 IEEE.
Keywords: Atom transportation; DNA transportation; Dynamic tweezers